Development of a Picture and Picture–Based Fable Book to Improve Elementary School Students’ Reading Comprehension: Pengembangan Buku Fabel Berbasis Picture and Picture untuk Meningkatkan Pemahaman Membaca - Risya Faiza Rizqi Wildan; Panca Dewi Purwati (Universitas Pendidikan Mandalika, 2026)
This study aimed to develop, validate, and examine the effectiveness of the Bintang Fauna fable book based on the Picture and Picture learning model in improving the reading comprehension skills of second-grade students at Semarang. The research employed a Research and Development (R&D) design using the Borg and Gall development model, which includes stages of needs analysis, product design, expert validation, revision, product trial, and effectiveness testing. The participants were second-grade elementary school students who were involved in the product trial. Data were collected through observation, interviews, questionnaires, expert validation sheets, and reading comprehension tests administered as pretests and posttests. The validation results showed that the developed fable book was highly feasible for classroom use, with material expert validation reaching 91.25% and media expert validation reaching 95%. These results indicate that the content, language, presentation, and visual design of the book were appropriate for young learners. The effectiveness test demonstrated a significant improvement in students’ reading comprehension after using the Bintang Fauna fable book, as shown by the paired sample t-test results and moderate N-Gain scores. Therefore, the Bintang Fauna fable book is feasible and effective as instructional material for improving elementary students’ reading comprehension.